2021
DOI: 10.1101/2021.01.07.425784
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Synthetic Promoter Designs Enabled by a Comprehensive Analysis of Plant Core Promoters

Abstract: Targeted engineering of plant gene expression holds great promise for ensuring food security and for producing biopharmaceuticals in plants. However, this engineering requires thorough knowledge of cis-regulatory elements in order to precisely control either endogenous or introduced genes. To generate this knowledge, we used a massively parallel reporter assay to measure the activity of nearly complete sets of promoters from Arabidopsis, maize and sorghum. We demonstrate that core promoter elements – notably t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 76 publications
2
25
0
Order By: Relevance
“…Functional enrichments also allowed the characterization of group 2 5'-uPLM signals in some genes involved in reactive oxygen metabolic processes. These signals were composed of more than 72% of uPLMs similar to RNA polymerase II binding sites, in agreement with previous observations showing a link between TATA-box and stress response, including the response to H 2 O 2 (21,46,58). Additionally, specific enrichments of the 3'-uPLMscontaining gene sets in group 1 compared to other groups revealed an involvement of these genes in ethylene response in both species.…”
Section: Discussionsupporting
confidence: 91%
“…Functional enrichments also allowed the characterization of group 2 5'-uPLM signals in some genes involved in reactive oxygen metabolic processes. These signals were composed of more than 72% of uPLMs similar to RNA polymerase II binding sites, in agreement with previous observations showing a link between TATA-box and stress response, including the response to H 2 O 2 (21,46,58). Additionally, specific enrichments of the 3'-uPLMscontaining gene sets in group 1 compared to other groups revealed an involvement of these genes in ethylene response in both species.…”
Section: Discussionsupporting
confidence: 91%
“…TATA box plays an important role in recruiting the basal transcription factors for assembly into transcription machinery. The TATA box is a key determinant of promoter strength (Jores et al, 2021). Previously, Hu et.…”
Section: Discussionmentioning
confidence: 99%
“…They have further expanded on this by developing a computational model that predicts promoter strength in collaboration with Travis Wrightsman and Ed Buckler. Jores showed that the model can be used to develop stronger promoter sequences via in silico evolution 94 . Jores hopes that these results will not only enable researchers to design strong promoters but also help them identify relevant target sites within promoters to edit promoter strength and consequently gene expression.…”
Section: Applications Of Genome Editing In Agriculturementioning
confidence: 98%
“…For example, Arabidopsis promoters, which were generally AT rich, were stronger than maize or sorghum promoters in the tobacco leaf reporter assay, whereas maize and sorghum promoters, which were generally GC rich, were stronger in the maize protoplast reporter assay. Core promoter elements like a TATA box, initiator, Y patch, BREu, BREd, or TCT initiator could affect promoter strength; some elements were associated with strong promoters in both tobacco and maize, while some had differential effects on promoter strength between tobacco and maize 94 …”
Section: Applications Of Genome Editing In Agriculturementioning
confidence: 99%